2015
DOI: 10.1159/000433560
|View full text |Cite
|
Sign up to set email alerts
|

MRI Susceptibility Changes Suggestive of Iron Deposition in the Thalamus after Ischemic Stroke

Abstract: Background: Iron accumulation has been linked to neuronal injury following cerebral ischemia. In animals, a hypointense signal on T2*-weighted (T2*-w) MRI correlated with iron deposits in remote brain regions following ischemic stroke. We aim to assess whether such signal changes are present in remote brain structures following ischemic stroke in humans. Methods: We analyzed T2*-w images of 36 patients with unilateral ischemic stroke and 36 healthy controls. Regions of interest (ROIs) consisted of the thalamus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…We speculate that, given a larger sample, TH may exhibit significantly increased susceptibility in PCAS patients than in healthy controls. Similar to our study, in a previous study that used signal intensity variation on T2 * -weighted images to reflect the changes of iron content, ischemic stroke patients, including those with infarcts in the distribution of PCA, showed increased iron accumulation in TH on the side ipsilateral to the infarct ( 43 ). Compared with healthy controls, both ACAS and PCAS patients exhibited significantly increased susceptibility in PU and GP.…”
Section: Discussionsupporting
confidence: 88%
“…We speculate that, given a larger sample, TH may exhibit significantly increased susceptibility in PCAS patients than in healthy controls. Similar to our study, in a previous study that used signal intensity variation on T2 * -weighted images to reflect the changes of iron content, ischemic stroke patients, including those with infarcts in the distribution of PCA, showed increased iron accumulation in TH on the side ipsilateral to the infarct ( 43 ). Compared with healthy controls, both ACAS and PCAS patients exhibited significantly increased susceptibility in PU and GP.…”
Section: Discussionsupporting
confidence: 88%
“…Our results provide additional information concerning the temporality of remote neurodegeneration after infarct. Van Etten et al (2015) reported a lower average T2*-signal intensity in manually drawn region of interest within the entire thalamus at a single slice level as early as Day 1 after stroke onset. However, T2* signal intensity suffers from high intra-and inter-examination variability and we believe our quantitative R2* mapping method is more robust, particularly with the unbiased 3D atlas-driven regions of interest that we used here.…”
Section: Discussionmentioning
confidence: 93%
“…We first computed parameters of the R2* histogram [histogram parameters (HP): 5th percentile, median, 95th percentile and full-width at half-maximum] within the whole thalamus ipsilateral and contralateral to infarct. An asymmetry index of R2* (van Etten et al, 2015) for each parameter of the histogram was also calculated with:…”
Section: Co-registrationmentioning
confidence: 99%
“…The MRI changes correspond with histological validation of reactive microglia/infiltrating macrophages and chronic accumulation of iron (8), indicating MRI as a potential tool to detect longitudinal changes in the secondary thalamic injury. Similarly, van Etten et al report hypointense signals in ipsilesional thalamus on T2 * -weighted MRI of unilateral ischemic stroke patients, suggesting accumulation of toxic iron in secondary thalamic injury (38). In patients with focal cortical infarction, a delayed shrinkage in the thalamus is detected by MRI scanned at late phase (31.6 ± 16.6 months after the initial stroke) (39).…”
Section: Methods and Strategies To Identify Secondary Thalamic Injurymentioning
confidence: 94%